Experimental investigation of prestressed two layer reinforced concrete beams. (29th December 2019) - Iskhakov, Iakov; Ribakov, Yuri; Holschemacher, Klaus; Kaeseberg, Stefan
Abstract: This study continues a series of investigation of two‐layer beams (TLB), performed by the authors. This series includes developing an idea of a TLB, testing steel fibered high strength concrete (SFHSC) as material, testing simple supported and continuous two‐span TLBs. The present research is focused on testing full‐scale prestressed simple supported TLBs (PTLBs). The study is aimed at investigating PTLBs behavior at four‐point bending and its comparison with that of nonprestressed ones. Like in the previous research stages, interaction of concrete layers in a PTLB was studied to prove the efficiency of such beams for real long‐span reinforced concrete beams. No de‐bonding between the SFHSC and normal strength concrete layers was observed up to the ultimate limit state of the tested beams that demonstrates proper interaction between the layers. Results, obtained in the present study, enable to recommend PTLB for further investigation of full‐scale reinforced concrete elements with longer spans (9–12 m) and their practical application as effective and economical bending elements.